2024
DOI: 10.3389/fnut.2024.1342787
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intermittent fasting on gut microbiota: a systematic review of human studies

Isa Paukkonen,
Elli-Noora Törrönen,
Johnson Lok
et al.

Abstract: BackgroundIntermittent fasting (IF) has gained popularity in interventions targeting overweight, obesity and metabolic syndrome. IF may affect the gut microbiome composition and therefore have various effects on gut microbiome mediated functions in humans. Research on the effects of IF on human gut microbiome is limited. Therefore, the objective of this systematic review was to determine how different types of IF affect the human gut microbiome.MethodsA literature search was conducted for studies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Systematic reviews have shown strong evidence that gastrointestinal microbial composition may exhibit two-way relationships with overweight and obese patients, suggesting that more information regarding microbial constituents that influence caloric balance is of paramount importance [20]. Moreover, as intervention studies have demonstrated that microbial composition may be responsive to behavioral modifications such as intermittent fasting, more information will be needed regarding the species composition deemed most important to these phenomena [21]. Finally, an understanding of the additional sites that harbor this organism may provide significant insight into the relationship between oral and gastrointestinal microbial prevalence and whether other significant interventions, such as fecal transplantation, may not be feasible against S. noxia [22].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have shown strong evidence that gastrointestinal microbial composition may exhibit two-way relationships with overweight and obese patients, suggesting that more information regarding microbial constituents that influence caloric balance is of paramount importance [20]. Moreover, as intervention studies have demonstrated that microbial composition may be responsive to behavioral modifications such as intermittent fasting, more information will be needed regarding the species composition deemed most important to these phenomena [21]. Finally, an understanding of the additional sites that harbor this organism may provide significant insight into the relationship between oral and gastrointestinal microbial prevalence and whether other significant interventions, such as fecal transplantation, may not be feasible against S. noxia [22].…”
Section: Introductionmentioning
confidence: 99%